2019
DOI: 10.1016/j.jveb.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Handler training improves decontamination of working canines with oil-based exposure in field conditions using disposable kits

Abstract: Exposure to contaminants in the field is a reality for deployed canines. To date, there is no data evaluating the benefits of training for handlers associated with canine decontamination efforts. The objective of our work was to investigate the impact of handler training on the reduction of oil-based contaminants in working canines. Canine teams (n = 10) were randomly assigned to either TRAINED or UNTRAINED groups. Each team (handler and dog) in the TRAINED group received 30-minutes of interactive training usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
0
6
0
1
Order By: Relevance
“…While previous work has shown that working canines are readily exposed to and contaminated with oil-based agents through direct contact [ 10 , 11 ], we are only just starting to understand the risk of contamination with water-based aerosols present in the environment. A simple field-expedient wipe-down procedure utilizing disposable towels saturated with 7.5% povidone-iodine solution may effectively reduce the burden of water-based aerosol contaminant on the coats of working canines without adversely affecting dermal pH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous work has shown that working canines are readily exposed to and contaminated with oil-based agents through direct contact [ 10 , 11 ], we are only just starting to understand the risk of contamination with water-based aerosols present in the environment. A simple field-expedient wipe-down procedure utilizing disposable towels saturated with 7.5% povidone-iodine solution may effectively reduce the burden of water-based aerosol contaminant on the coats of working canines without adversely affecting dermal pH.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence, indicative of simulated aerosol contamination, was documented in each of the quadrants on the dorsal aspect of the canine following wipe-down and compared with the control quadrant via digital imaging using a Canon T5i DSLR (Canon Inc., Tokyo, Japan) camera positioned 45 cm (±5) from the canine. The removal of droplets (i.e., physical reduction of simulated contaminant) was scored as fluorescence reduction utilizing a method previously published [ 10 , 11 , 12 ]. The scoring method was applied utilizing two blinded and independent reviewers with 82% agreement.…”
Section: Methodsmentioning
confidence: 99%
“…While previous work has shown that working canines are readily exposed to and contaminated with oil-based agents through direct contact (5,6), we are only just starting to understand the risk of contamination with water-based aerosols present in the environment. A simple field-expedient wipe-down procedure utilizing disposable towels saturated with 7.5% povidone-iodine solution may effectively reduce the burden of water-based aerosol contaminant on the coats of working canines without adversely affecting dermal pH.…”
Section: Discussionmentioning
confidence: 99%
“…Los caninos de trabajo están frecuentemente expuestos a ambientes peligrosos con alto potencial de contaminación (Perry et al, 2020). La contaminación ambiental puede ocurrir de muchas maneras (química, biológica, radiológica o nuclear) (Powell et al, 2019). Por otra parte, en casos de terremotos pueden existir rupturas de tuberías que ocasionan contaminación por microorganismos, represamiento de aguas o productos químicos industriales tóxicos como el cloruro de hidrógeno, el amoníaco o el tolueno que pueden afectar al equipo canino (Perry, 2021).…”
Section: • Discusiónunclassified